Colecistectomía laparoscópica: experiencia inicial - Morelli, Raúl; Bermúdez, Jorge; Veirano, Gustavo (Cirugía del Uruguay, 1992)
Laparoscopic cholecystectomy is rapidly becoming the procedure of election for treatment of symptomatic vesicular lithiasis. Between December 1990 and August 1991 the authors operated on 79 patients. Operatin gime was of 84 ·. lntraoperative cholangiography was carried out in 61% of the patients. Conversion to open surgery took place in 3.8%. There was no mortality. 83% of the patients were discharged from hospital befare the first 24 hours after the operation were due. Return to work varied from 5 to 30 days.